Pinning magnetic domain via patterning artificial lattice under amorphous magnetic layer - Wu, TH; Wu, JC; Chen, BM; Shieh, HPD (My University, 1999)
A novel method for pinning magnetic domains on pre-formatted pinning sites has been developed for perpendicular magnetic anisotropy magneto-optical (MO) thin film media. The pinning sites were artificial lattices made by patterning a layer of gold grid on the substrate using electron beam lithography. Compared with the work proposed using photolithography, our method showed the ability of making smaller pinning domains. Moreover, compared with our previous work using the same electron beam lithography method and creating hole arrays on polymethyl methacrylate, this new method could stand higher film deposition temperatures and avoid the MO films rapid deterioration on a PMMA substrate. In order to investigate the domain pinning behavior we did several different procedures and observed their corresponding domain pinning layouts. Magnetic domains were found to be pinned inside the lattice and resembled the geometric shapes of the lattice. The pinned domains acquired the shape of the lattice. In this article, the star-shaped type of geometry of grid arrays is presented. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: pinned magnetic domain; E-beam lithography; patterned substrate; magneto-optical